Social work education : indigenous perspectives - Roy, Sanjoy(ed.) (New Delhi Sage, 2021)
"Social work education as a concept refers to the integration of the core knowledge, values and critical skills and competencies that social workers must acquire for competent practice in their fields of work. Social work education is an emerging professional area in India and faces unique challenges such as the absence of local orientation and lack of synchronization between classroom learning and field realities"--
Keywords: Social service; Social work education